Synthesis of Methyl Ester from Microalgae Chlorella sp. TAD Using the In-Situ Transesterification Method - Telussa, Ivon; Fransina, Eirene G.; Kalauw, Kalsum (Politeknik Negeri Malang, 2024)
Synthesis of methyl ester from Chlorella sp. TAD microalgae was carried out using the in-situ transesterification method. This study aims to determine the methyl ester composition of Chlorella sp. TAD microalgae using the in-situ transesterification method. The in-situ transesterification method is a modified method that allows extraction and transesterification into methyl ester products in one process simultaneously. The in-situ transesterification process lasted 8 hours, followed by a distillation process to remove the n-hexane content and an oven for 2 hours to evaporate the remaining water. The results of the analysis using GC-MS to determine the chemical content of the methyl ester compound from Chlorella sp. TAD, showed the methyl ester composition of 7,10-hexadecanoic methyl ester, 8,11,14-docosatrienoic methyl ester, 9-hexadecanoic methyl ester, hexadecanoic methyl ester, heptadecanoic methyl ester, 10-octadecenoic methyl ester, octadecenoic methyl ester, 9,12-octadecadienoic methyl ester, 10-octadecenoic methyl ester, 2-hexyl cyclopropaneoctanoic methyl ester, eicosanoic methyl ester, 10-heptadecen-8-ynoic acid methyl ester, nonahexacontanoic methyl ester, and tetracosanoic methyl ester.